2013
DOI: 10.2214/ajr.12.9186
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Invasion of the Nipple-Areolar Complex of the Breast: Usefulness of Breast MRI

Abstract: MRI is a useful method for the evaluation of malignant invasion of the nipple-areolar complex. Nipple-areolar complex enhancement with thickening could suggest the possibility of nipple involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 19 publications
4
41
0
4
Order By: Relevance
“…The rates of tumour NAC involvement in the literature are inconsistent [14][15][16][17][18][19][20][21] likely due to different pathological protocols for NAC evaluation and variable accuracy of clinical and pathological data collection. For example, a recent systematic review of the literature showed that only 6.4% of the nipple cores of 2477 NAC sparing mastectomies were involved with tumour [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of tumour NAC involvement in the literature are inconsistent [14][15][16][17][18][19][20][21] likely due to different pathological protocols for NAC evaluation and variable accuracy of clinical and pathological data collection. For example, a recent systematic review of the literature showed that only 6.4% of the nipple cores of 2477 NAC sparing mastectomies were involved with tumour [13].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous retrospective study [18], by setting the cut-off of the tumour-NAC distance at 10 mm, MRI outperformed MX in the prediction of NAC involvement with a sensitivity of 100% versus 71% and a specificity of 66% versus 63% respectively. Moon et al [21] in a retrospective analysis of 51 breast cancers reported that NAC enhancement at MRI had a sensitivity of 93.8% and a specificity of 85.7%. In the current prospective study, axial tumour-NAC distance at MRI with a cut-off set at 10 mm had lower sensitivity (53.6% versus 100%), but higher specificity (88.6% versus 66.0%) as compared to our retrospective study [18], and its overall accuracy was slightly increased by setting the cut-off at 5 mm (78.5% versus 75.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Also, breast MRI can describe morphological appearance and enhancement patterns of NAC as well as accurate determination of tumor size and location [13][14][15][16][17]. The sensitivity and specificity of 1.5-T MRI were 56%-93.8% and 85.7%-95%, respectively, in previous studies [1,9]. Comparing 1-T and 1.5-T magnetic resonance (MR) systems, 3-T MRI showed increased signalto-noise ratio (SNR), spatial resolution, and temporal resolution [12].…”
Section: Introductionmentioning
confidence: 90%
“…NAC involvement was defined as three categories on the basis of previous studies [1,9,20,21]. Firstly, continuity to NAC was defined as linear enhancement direct from primary mass (Fig.…”
Section: Image Analysismentioning
confidence: 99%
See 1 more Smart Citation